Analysis of Budget Realization to Assess the Effectiveness and Efficiency of Expenditure Budget in the Financial Affairs Division (Bidkeu) of the Central Java Regional Police for Fiscal Year 2024 - Wyna Nur Azizah; Nurfauziah Nurfauziah (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study aims to analyze budget realization in order to assess the effectiveness and efficiency of expenditure management at the Financial Affairs Unit (Bidkeu) of the Central Java Regional Police for the 2024 fiscal year, based on the Value for Money principle. A quantitative approach was employed, with the unit of analysis comprising the Bidkeu work unit, including Subbag Renmin, Subbidal Verif, and Subbidal Bia and Apk, focusing on personnel expenditure, goods expenditure, and capital expenditure. Primary data were collected through direct observation during a four-month internship, short interviews with relevant staff, and supported by financial documents such as the Budget Realization Report (LRA) and the Budget Implementation Document (DIPA). Data analysis was conducted using descriptive quantitative methods by calculating effectiveness and efficiency ratios in accordance with the criteria set out in Ministry of Home Affairs Regulation No. 690.900.327 of 1996. The findings indicate that overall budget management demonstrates a very high level of effectiveness, as budget realization exceeded the established targets, although efficiency remains at a moderately efficient level due to incomplete budget absorption. Variations were found across expenditure types, while efficiency analysis revealed opportunities for improved cost control. Overall, the results confirm that the implementation of the Value for Money principle supports the strengthening of Good Governance in public financial management.